Oncolytic Virotherapy for Relapsed, IDH-Mutant, Grade 3 Astrocytoma: A New Promising Approach – A Case Report - Benjamin Gesundheit; Jayadeepa Srinivas Raju; Chaim Y. Brauns; Christine Weisslein; Harald Schmoll; Ronald Ellis; Yehudit Posen; Andreas Schmitz; Hüseyin Sahinbas (Case Reports in Oncology)
Introduction: IDH-mutant astrocytomas are high-grade gliomas with a poor prognosis. Transformation to glioblastoma multiforme is common, which further shortens overall survival and frequently renders the tumor inoperable. Oncolytic viruses (OVs) have been shown to be safe and effective agents for the treatment of some malignant brain tumors. Intra-tumoral application may further enhance their therapeutic potential. Case Presentation: This report presents a case of a 37-year-old female patient with advanced relapsed grade 3 astrocytoma, with multiple foci, including one along the rim of the left fronto-parietal post-op cavity, who was treated with a one-shot OV regimen via an Ommaya reservoir (IO-OV), with the catheter tip placed intra-tumorally. Adjunct electro-hyperthermia therapy was also provided. No evidence of disease (NED) was achieved after the first cycle of IO-OV and was maintained for 9 months until the non-vaccinated patient contracted COVID-19, after which aggressive and refractory relapse occurred. Conclusion: OV therapy proved to induce significant clinical improvements and radiological NED for this incurable astrocytoma. This promising modality should be evaluated as an adjunct to first-line therapy for inoperable brain tumors.